Bovinocultura de leite - Manejo e Sanidade - Maia, Flávia Luíza Ferreira Fideles e (Universidade Federal do Tocantins, 2024)
The supervised internship was conducted at Fazenda Santa Maria, located in Jataí – GO, during the period from August 16 to October 26, 2023, encompassing a total of 390 hours. The internship focused on the field of animal handling and health, with an emphasis on medical clinic for dairy cattle and calf management. The activities took place under the supervision of veterinarian Luiz Cássio Silva Morais, with the collaboration of veterinarian Wânia Domingos Oliveira. This report outlines all the physical facilities of the property, as well as the activities carried out during the internship. Additionally, it presents a case of cervical prolapse and its on- site resolution.